Exploring polychrome traces on 11th century clay figurines from Schroda, northern South Africa. - Loubser, Maggi (University of Pretoria, 2025)
Mini Dissertation (MSocSci (Cultural Heritage, Heritage Conservation))--University of Pretoria, 2024.